Development of a patient-reported outcome measure of activity and participation (the OKSAPQ) to supplement the Oxford knee score - Dawson, J; Beard, D; McKibbin, H; Harris, K; Jenkinson, C; Price, A (2014)
The primary aim of this study was to develop a patient-reported Activity and Participation Questionnaire (the OKS-APQ) to supplement the Oxford knee score, in order to assess higher levels of activity and participation. The generation of items for the questionnaire involved interviews with 26 patients. Psychometric analysis (exploratory and confirmatory factor analysis and Rasch analysis) guided the reduction of items and the generation of a scale within a prospective study of 122 relatively young patients (mean age 61.5 years (42 to 71)) prior to knee replacement. A total of 99, completed pre-operative and six month postoperative assessments (new items, OKS, Short-Form 36 and American Knee Society Score). The eight-item OKS-APQ scale is unidimensional, reliable (Cronbach's alpha 0.85; intraclass correlation coefficient (ICC) 0.79; or 0.92 when one outlier was excluded), valid (r > 0.5 with related scales) and responsive (effect size 4.16). We recommend that it is used with the OKS with adults of all ages when further detail regarding the levels of activity and participation of a patient is required. © 2014 The British Editorial Society of Bone and Joint Surgery.